2021
DOI: 10.1152/ajplung.00376.2020
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine CX3CL1/fractalkine regulates immunopathogenesis during fungal-associated allergic airway inflammation

Abstract: Individuals that present with difficult-to-control asthma and sensitivity to one or more fungal species are categorized as a subset of severe asthma patients belonging to a group herein referred to as severe asthma with fungal sensitization (SAFS). We have previously reported the identification of numerous cytokines and chemokines that were elevated in human asthmatics that were sensitized to fungi vs. non-fungal sensitized asthmatics. Here, we show that the unique chemokine CX3CL1 (fractalkine) is elevated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In contrast, we demonstrated that IL-1RA was an attractive and efficacious immunoprotective therapeutic for improving fungal asthma severity (21). Ongoing work in our laboratory has also identified CX3CL1 as an immunoprotective mediator during fungal asthma (26). YKL-40 has been implicated in non-type 2 asthma due to its relationship with mediators associated with IL-17-mediated inflammation (15,46).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, we demonstrated that IL-1RA was an attractive and efficacious immunoprotective therapeutic for improving fungal asthma severity (21). Ongoing work in our laboratory has also identified CX3CL1 as an immunoprotective mediator during fungal asthma (26). YKL-40 has been implicated in non-type 2 asthma due to its relationship with mediators associated with IL-17-mediated inflammation (15,46).…”
Section: Discussionmentioning
confidence: 88%
“…37 Signaling by this chemokine receptor preserves lung function in fungal-induced allergic airway inflammation, which is mediated via a novel regulatory mechanism. 38 Our results…”
Section: Discussionmentioning
confidence: 63%
“…CX3CR1 is suppressed in circulating non‐classical monocytes from severe asthmatic patients 37 . Signaling by this chemokine receptor preserves lung function in fungal‐induced allergic airway inflammation, which is mediated via a novel regulatory mechanism 38 . Our results suggest an anti‐inflammatory role of this specific subtype, reversely linked to ambient PM 2.5 levels.…”
Section: Discussionmentioning
confidence: 70%
“…CX3CR1 is suppressed in circulating non-classical monocytes from severe asthmatic patients (29 ). Signaling by this chemokine receptor preserves lung function in fungal-induced allergic airway inflammation, which is mediated via a novel regulatory mechanism (30 ). Our results suggest an anti-inflammatory role of this specific subtype, reversely linked to ambient PM 2.5 level.…”
Section: Increased Frequency Of Cluster 4 [Cd16mentioning
confidence: 67%